Higher order expectations, illiquidity, and short-term trading - Giovanni Cespa; Xavier Vives (Center for Economic Studies and ifo Institute (CESifo), 2011)
We propose a theory that jointly accounts for an asset illiquidity and for the asset price potential over-reliance on public information. We argue that, when trading frequencies differ across traders, asset prices reflect investors' Higher Order Expectations (HOEs) about the two factors that influence the aggregate demand: fundamentals information and liquidity trades. We show that it is precisely when asset prices are driven by investors' HOEs about fundamentals that they over-rely on public information, the market displays high illiquidity, and low volume of informational trading; conversely, when HOEs about fundamentals are subdued, prices under-rely on public information, the market hovers in a high liquidity state, and the volume of informational trading is high. Over-reliance on public information results from investors' under-reaction to their private signals which, in turn, dampens uncertainty reduction over liquidation prices, favoring an increase in price risk and illiquidity. Therefore, a highly illiquid market implies higher expected returns from contrarian strategies. Equivalently, illiquidity arises as a byproduct of the lack of participation of informed investors in their capacity of liquidity suppliers, a feature that appears to capture some aspects of the recent crisis.
Keywords: G10; G12; G14; 330; expected returns; multiple equilibria; average expectations; over-reliance on public information; Beauty Contest; Kapitalertrag; Erwartungstheorie; Wertpapierhandel; Informationsverhalten; Marktliquidität; Börsenkurs; Theorie